Lack of Association between HLA Class II Alleles and In Vitro Replication Capacities of Recombinant Viruses Encoding HIV-1 Subtype C Gag-Protease from Chronically Infected Individuals - Wright, Jaclyn K.; Brumme, Zabrina L.; Julg, Boris; Stok, Mary van der; Mncube, Zenele; Gao, Xiaojiang; Carlson, Jonathan M.; Goulder, Philip J. R.; Walker, Bruce D.; Brockman, Mark A.; Ndung'u, Thumbi (Journal of Virology, 2011)
It is unknown whether favorable HLA class II alleles may attenuate HIV-1 through selection pressure in a manner similar to that of protective HLA class I alleles. We investigated the relationship between HLA class II alleles and in vitro replication capacities of recombinant viruses encoding HIV-1 subtype C Gag-protease from chronically infected individuals. No associations were found between individual alleles and lower replication capacity, suggesting no significant HIV-1 attenuation by HLA class II-restricted Gag-specific CD4+ T cell immune pressure.